Research on Uninterrupted Power Supply Technology for Separate Winding Powered Converter - HU Jingyu; XU Guangwei; LIU Jiancheng; LUO Wenguang; PENG Yun (Kongzhi Yu Xinxi Jishu)
If the auxiliary converter and train power supply system of electric locomotive and EMU use separate windings for power supply, there is a problem of power interruption during pantograph passing neutral sections. Aiming at this problem, it proposed an uninterrupted power supply technology for separate winding powered converter, which is suitable for multiple topologies. Resonance overvoltage of traction transformer that severely restricts the uninterrupted power supply technology was analyzed and effective solutions to avoid resonance interval were proposed. Simulation test results verify the correctness and feasibility of the overall technical solution.